Youth multidimensional political activism between singularization and mutualism: the case of Up network - Lidia Lo Schiavo; Paola Rebughini (Cambio)
In the past two decades, research in both “social movements studies” and “critical youth” studies has recorded the growing criticism, by youth political activism, of the individualizing processes characteristic of the neoliberal turn. Based on research conducted in Italy with the new network of activists Up, the article analyses the search for a new equilibrium between processes of singularization, and a community life where solidarity, cooperation and mutualism can build local forms of the common and the collective. In the first part of the article, we describe our analytical tools such as singularization, mutualism and generation, and the way in which they can highlight current political imagination of Italian youth; in the second part we present the results of our investigation and the way in which interviewees claim to belong to a wider frame of the transformation of politics in individualized societies.